Patients-Reported Oral Manifestations in Coeliac Disease and Inflammatory Bowel Diseases: An Italian Survey - Giulia Valentini; Silvia D’Agostino; Elisabetta Ferrara; Marco Dolci (Oral, 2023)
Inflammatory Bowel Diseases (IBDs), including Ulcerative Colitis (UC), Crohn’s Disease (CD), Irritable Bowel Syndrome (IBS), and Coeliac Disease (CoD), primarily affect the intestinal tract but show some extra-intestinal manifestations affecting the skin, joints, liver, pancreas, and lungs. The aim of this survey was to define how often these intestinal conditions show oral manifestation. The study involved 46 patients of 56 recruited at the beginning, with a mean age of 42 ± 13.64 and a sex distribution of 67.4% (31) female and 32.6% (15) male. Everyone was sent a questionnaire of four multiple-choice questions about the type of their bowel disease, the time of the diagnosis, the major symptoms which led to the disease discover, and finally their oral symptoms. According to the results, 65.52% referred to oral manifestations, especially canker sores and burning sensation. The oral involvement suggests that multidisciplinary management and therapy are mandatory, with close monitoring and follow-up interfacing with other specialists. Finally, dental practitioners have to be aware of this possible oral effect in IBDs and CoD patients.